Bài 18.Rút gọn rồi tính giá tri các biểu thức sau
1) \(5x^2-2x.\left(3x+\frac{3}{2}\right)\)tại x=3
2) \(3x\left(x-4y\right)-\frac{12}{5}y\left(y-5x\right)\)tại x=4:y=5
3)\(\left(x-2\right)^2-\left(x+7\right)\left(x-7\right)\)tại x=3
4) \(x^2+12x+36\)tại x=64
5) \(\left(x-3\right)^2-\left(x+4\right)\left(x-4\right)\)tại x-1
6) \(\left(3x+2y\right)^2-4y\left(3x+y\right)\)tại x=\(-\frac{1}{3}\):y=1
a) \(5x^2-2x\left(3x+\frac{3}{2}\right)=-x^2-3x=-x\left(x+3\right)=-3\left(3+3\right)=-18\)
b) \(3x\left(x-4y\right)-\frac{12}{5}y\left(y-5x\right)=3x^2-\frac{12}{5}y^2=3\left(x^2-\frac{4}{5}y^2\right)\)
\(=3\left(4^2-\frac{4}{5}.5^2\right)=3.\left(-4\right)=-12\)
c) \(\left(x-2\right)^2-\left(x+7\right)\left(x-7\right)=x^2-4x+4-x^2+49=-4x+53=-4.3+53=41\)
d) \(x^2+12x+36=\left(x+6\right)^2=\left(64+6\right)^2=70^2=4900\)
e) \(\left(x-3\right)^2-\left(x-4\right)\left(x+4\right)=x^2-6x+9-x^2+16=-6x+25=-6\left(-1\right)+25\)
= 31
f) \(\left(3x+2y\right)^2-4y\left(3x+y\right)=9x^2+12xy+4y^2-12xy-4y^2=9x^2=9\left(-\frac{1}{3}\right)^2=1\)
a, \(5x^2-2x\left(3x+\frac{3}{2}\right)=-x^2-3x\)
Thay x = 3 vào biểu thức trên ta cs : \(-3^2-3.3=-9-9=-18\)
b, \(3x\left(x-4y\right)-\frac{12}{5}y\left(y-5x\right)=3x^2-\frac{12}{5}y^2\)
Thay x = 4 ; y = 5 vào biểu thức trên ta có : \(3.4^2-\frac{12}{5}.5^2=-12\)